Monitoring the Philippine Economy Year-End Report for 2014 - Conchada, Mitzie Irene P. (Animo Repository, 2015)
Despite doubts over growth prospects and challenges in the external market, the Philippine economy attained a solid 6.1 percent growth in 2014.